The black book : Woodrow Wilson's secret plan for peace - Reisser, Wesley J. (Lexington Books, 2012)
This book is the first ever in depth look at the geographic peace plans used by the United States at the end of World War I. It analyzes the negotiation and implementation of these plans and analyzes the lasting impact of the territorial settlements on the ensuing history of Europe and the Middle East.